Propagation of nutrients and metals after the 2022 Hermit's Peak-Calf Canyon gigafire - Kaphle, Asmita; Rodríguez, Lina; Tunby, Paige; Nichols, Justin; Khandelwal, Aashish; Joseph, Eric; Aldred, Jennifer; Van Horn, David J.; González-Pinzón, Ricardo (Frontiers in Water, 2025)
The increasing severity and frequency of wildfires in forested watersheds pose significant challenges to water quality management. This study examines the impacts of the 2022 Hermit's Peak-Calf Canyon gigafire, the largest wildfire in New Mexico's history. The wildfire burned over 1,382 km2, affecting a key watershed that supplies drinking water to Las Vegas, NM. We conducted a longitudinal assessment of post-fire water quality dynamics across a 170 km fluvial network, analyzing flow, water quality parameters, nutrient and metal concentrations, and mobilization patterns. We found that post-fire nutrient concentrations exceeded pre-fire medians by up to two orders of magnitude. Our analyses revealed solute-specific transport patterns that are difficult to predict with static watershed- or fire-specific characteristics (e.g., burned area and percent severities). NH4+, PO3-, and NO2- were closely and positively associated with discharge and turbidity near the burn perimeter, while NO3- and TON exhibited strong mobilization trends ~170 km downstream. In contrast to nutrients, calcium, magnesium, and manganese levels showed no significant pre- vs. post-fire shifts, while concentrations of trace metals like Cr3+, Pb2+, Zn2+, and Sr2+ surpassed background levels and public health thresholds. Our findings emphasize the significant propagation of wildfire disturbances over hundreds of kilometers and suggest the need for integrated watershed management strategies, including the management of large-scale flood control mechanisms to mitigate the far-reaching impacts of water quality disturbances post-fire.